Microbial symbiosis and the control of vector-borne pathogens in tsetse flies, human lice, and triatomine bugs. (1st September 2013) - Sassera, Davide; Epis, Sara; Pajoro, Massimo; Bandi, Claudio
Abstract : Symbiosis is a widespread biological phenomenon, and is particularly common in arthropods. Bloodsucking insects are among the organisms that rely on beneficial bacterial symbionts to complement their unbalanced diet. This review is focused on describing symbiosis, and possible strategies for the symbiont-based control of insects and insect-borne diseases, in three bloodsucking insects of medical importance: the flies of the genus Glossina, the lice of the genus Pediculus, and triatomine bugs of the subfamily Triatominae . Glossina flies are vector of Trypanosoma brucei, the causative agent of sleeping sickness and other pathologies. They are also associated with two distinct bacterial symbionts, the primary symbiont Wigglesworthia spp., and the secondary, culturable symbiont Sodalis glossinidius . The primary symbiont of human lice, Riesia pediculicola, has been shown to be fundamental for the host, due to its capacity to synthesize B-group vitamins. An antisymbiotic approach, with antibiotic treatment targeted on the lice symbionts, could represent an alternative strategy to control these ectoparasites. In the case of triatominae bugs, the genetic modification of their symbiotic Rhodococcus bacteria, for production of anti- Trypanosoma molecules, is an example of paratransgenesis, i.e. the use of symbiotic microorganism engineered in order to reduce the vector competence of the insect host.